Anatomical and physiological contributions of nasal turbinate vessels and lymphatics to the pathogenesis of nasal congestion in recurrent headaches: a pilot study - Chmielecki, Jacob M.; Vemula, Aishwarya; Schwartz, Joyce G.; Gelfond, Jonathan A.; Phillips, William T. (Frontiers in Pain Research, 2025)
IntroductionThe aim of this study was to determine if specific anatomical changes were present in patients with recurrent headaches including patients with chronic migraines, chronic tension-type headaches, and daily persistent headaches. A retrospective study of 200 patients was performed to evaluate the potential of measuring the amount of nasal blood pool activity (nasal congestion) as a predictive marker for recurrent headaches.MethodsA cohort analysis was performed involving patients who had been referred to the Nuclear Medicine Clinic over a 3-year period for whole-body blood pool scans. The scans were evaluated by region of interest (ROI) analysis of nasal and heart max pixel count ratios (NHMRs) to determine an association between nasal blood pooling activity and recurrent headaches at the time of the initial scan and in follow-up evaluations over a period of 3–6 years.ResultsSignificantly greater NHMRs were observed in 122 patients with chronic headaches at the time of referral for their initial whole-body blood pool scan when compared with those patients without recurrent headaches (p = 0.004; OR 10.5; 95% CI 2.22–56.7). An additional 15 patients, for a total of 137, developed recurrent headaches following their initial scan and before their follow-up evaluation. NHMRs were also significantly increased in the additional patients when compared to those without recurrent headaches (p = 0.004; OR 12.3; 95% CI 2.34–75.5).ConclusionPatients with recurrent headaches have significantly increased nasal activity as observed on 99mTc-MDP whole-body blood pool scans, supporting the hypothesis that nasal lymphatic dysfunction plays a role in the etiology of recurrent headaches. This research highlights a novel diagnostic use of the whole-body blood pool scan for the assessment of nasal turbinate vasodilation as well as a possible new target for the treatment of recurrent headaches.